(untitled) (Research, Society and Development, 2025)
This study aims to analyze whether there are accounting inconsistencies in the balance sheets of the State of São Paulo for the years 2022 and 2023, using the Disclosure Theory as theoretical support. The data for this investigation were extracted from the Transparency Portal of the state of São Paulo, the Accounting and Tax Information System of the Brazilian Public Sector – SICONFI, the website Integrated View of the Debts of the Union, States, Federal District and Municipalities, and the System for Analysis of Public Debt, Credit Operations and Guarantees of the Union, States and Municipalities – SADIPEM. The results revealed the existence of accounting inconsistencies in the Balance Sheets for the years 2022 and 2023 of the State of São Paulo: discrepancy between the amounts of Payable Liabilities and Real Liabilities; inconsistencies in the amounts of Remaining Payables processed and not processed; The assets and liabilities do not represent the financial and equity situation of the State of São Paulo, as discrepancies were found in the amounts disclosed. Finally, based on the Theory of Disclosure, it is concluded that the amounts recorded in the balance sheets for the years 2022 and 2023 do not adequately reflect the real situation of the Public Assets of the State of São Paulo.